Heterogeneity of Cause, Care, and Prognosis in Severe Acute Kidney Injury in Hospitalized Patients: A Prospective Observational Study. Issue 1 (December 2019) - Aglae, Cedric; Muller, Laurent; Reboul, Pascal; Cariou, Sylvain; Saber Davide, Barbar; Trusson, Remi; Messikh, Ziyad; De Brauwere, David-Paul; Lefrant, Jean-Yves; Moranne, Olivier
Background: KDIGO (Kidney Disease: Improving Global Outcomes) defines acute kidney injury (AKI) solely by serum creatinine (SCr) and urine output variation. Severe AKI is a syndrome covering various clinical situations. Objective: To describe severe AKI heterogeneity by department of hospitalization. Design: This is a prospective observational single-center study. Setting: Adult patients hospitalized in a French tertiary hospital from August 2016 to December 2017. Patients: All adults with severe AKI, defined by dialysis for AKI or an increase in SCr above 354 μmol/L. Measurements: Patient characteristics, clinical and laboratory presentation, AKI cause, medical indication for renal replacement therapy (RRT), planned palliative care, and vital status 30 days after severe AKI. Methods: A global description of patient characteristics, care, and prognosis and comparison by department of hospitalization: intensive care unit (ICU), nephrology, and others. Results: The study included 480 patients (73% men, median age: 72 years, range: 64-83), with medical histories including cardiovascular disease, diabetes, cancer, and chronic kidney disease. Principal causes were sepsis (104; 22%), hypovolemia (98; 20%), obstructive AKI (84; 18%), acute tubular necrosis (ATN; 74; 15%), and cardiorenal syndrome (51; 11%). Severe AKI was diagnosed in the ICU for 188 (39%) patients, the nephrology department for 130 (27%), and in other wards for 162 (34%). Patient characteristics differed by department for age, comorbidity, cause, and RRT use and indications. Palliative care was planned for 72 (15%) patients, most frequently in other wards. Limitations: We studied a subgroup of stage 3 KDIGO AKI patients in a single center without cardiac surgery. Conclusion: Patients hospitalized for severe AKI have frequent and various comorbidities, different clinical presentations, care, hospitalization in various departments, and different prognosis. The heterogeneity of this severe AKI implies the need for personalized care, which requires prognostic tools that include information besides SCr and diuresis.